Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/sla.0b013e3182682f27
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness, Compliance, and Critical Factors for Implementation of Safety Checklists in Surgery

Abstract: Checklists are effective and economic tools that decrease mortality and morbidity. Compliance of surgical staff with checklists was good overall. Further research in particular relating to implementation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
239
2
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(295 citation statements)
references
References 44 publications
11
239
2
23
Order By: Relevance
“…Key areas that facilitated good implementation were the presence of a checklist champion, effective communication and teamwork, and training of [18] reported that most studies were done in HICs. Haynes et al [4] had four sites in LMICs, and six of the safety indicators had compliance rates of 0%, 18.1%, 92.1% and 56.7% at the four hospitals.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Key areas that facilitated good implementation were the presence of a checklist champion, effective communication and teamwork, and training of [18] reported that most studies were done in HICs. Haynes et al [4] had four sites in LMICs, and six of the safety indicators had compliance rates of 0%, 18.1%, 92.1% and 56.7% at the four hospitals.…”
Section: Researchmentioning
confidence: 99%
“…In a systematic review of 21 studies, Borchard et al [18] concluded that the overall compliance rate ranged from 12% to 100%. Key areas that facilitated good implementation were the presence of a checklist champion, effective communication and teamwork, and training of [18] reported that most studies were done in HICs.…”
Section: Researchmentioning
confidence: 99%
“…Apparently, a more elaborate explanation is needed for a better understanding of the purpose of the EYEpad, both for patients and nurses. Previous work has suggested the success of checklist implementation largely depends on a clear explanation of the 'why' and 'how' [21]. A better understanding of the 'why' in this study could further improve the feasibility.…”
Section: Limitationsmentioning
confidence: 99%
“…Information technology may substantially contribute to engaging patients in activities to improve patient safety [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This clinician-led 'in the field' action research allows work flow and clinician acceptability to be built into the iterative process while minimising time or money foregone in the event of failure. Such an approach underpinned highly successful programs for preventing catheter-related bloodstream infections in ICUs 86 and reducing operating theatre mishaps, 87 with resultant cost savings.…”
Section: Convert Health Care Institutions Into Rapidly Learning Organmentioning
confidence: 99%